Pengaruh Kesadaran Kesehatan dan Perceived Barriers terhadap Attitude Toward Organic Food dan Dampaknya terhadap Minat Beli - Wenny Pebrianti; Ilmira Rosalin (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2021)
The purpose of this study is to examine and analyze the effect of health consciousness and perceived barriers in predicting attitude and purchase intention within the context of organic food. Non probability sampling technique is applied. Data were obtained from 120 respondents in Pontianak who are interested in buying organic vegetables. Data were analyzed with path analysis method by using SPSS 21.0 software programs. The results of this study indicate that the attitude toward organic food is significantly influenced by health consciousness and it is not significantly influenced by perceived barriers. Meanwhile, the purchase intention of organic vegetable is significantly influenced by attitude toward organic food and it is not significantly influenced by health consciousness and perceived barriers.